Исследование статистических свойств выборочных характеристик, полученных методом мультифарктального флуктуационного анализа - Аврамова, Е. В. (ХНУРЕ, 2012)
Work is devoted to research statistic properties of method of multifractal detrended fluctuation analysis, especially in the case of slight size of time series. Also question how to discriminate between monofractals and multifractals was studied.
Keywords: мультифакторная концепция; спектр фрактальных размерностей; МФДФА; показатель Херста